2011
DOI: 10.1080/00220388.2011.579115
|View full text |Cite
|
Sign up to set email alerts
|

Aid Absorption and Spending in Africa: A Panel Cointegration Approach

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…We employed five different dynamic models in the table above FMOLS, DOLS, GMM, PMG and DFE due to their statistical power over other tests. Aside that FMOLS and DOLS supports I(1) variables and GMM is done on fact that our N(Cross sections) is greater than T. However, PMG is justified on the assumption of (Arif et al, 2017;Attiaoui et al, 2017;Martins, 2011;Njoupouognigni, 2010;Pesaran et al, 1999). Furthermore, PMG, GMM tests take into consideration endogeneity problem and DOLS takes care of endogenous and lag and to obtain more robust result is obtained see, (Chudik et al, 2017;Eberhardt and Presbitero, 2015;Égert, 2015;Suliková et al, 2015;Woo and Kumar, 2015).…”
Section: Empirical Results and Discussionmentioning
confidence: 97%
“…We employed five different dynamic models in the table above FMOLS, DOLS, GMM, PMG and DFE due to their statistical power over other tests. Aside that FMOLS and DOLS supports I(1) variables and GMM is done on fact that our N(Cross sections) is greater than T. However, PMG is justified on the assumption of (Arif et al, 2017;Attiaoui et al, 2017;Martins, 2011;Njoupouognigni, 2010;Pesaran et al, 1999). Furthermore, PMG, GMM tests take into consideration endogeneity problem and DOLS takes care of endogenous and lag and to obtain more robust result is obtained see, (Chudik et al, 2017;Eberhardt and Presbitero, 2015;Égert, 2015;Suliková et al, 2015;Woo and Kumar, 2015).…”
Section: Empirical Results and Discussionmentioning
confidence: 97%
“…() has shown that there exists a possibility of a long‐run cointegration relation among series of differing order of integration (that is I(0) and I(1)). Based on this—and following the approach of Frimpong and Adu (), Martins () and Morshed ()—we proceed to examine the cointegration relationship among the variables in this study.…”
Section: Estimation Resultsmentioning
confidence: 99%
“…Ogundari and Awokuse (2018) indicated that the educational measure of human capital makes a smaller contribution to economic growth than the health measure of human capital. Martins (2011) estimated that two-thirds of aid receipts in African countries are used to finance imports. The other part is used to increase international reserves.…”
Section: Does Human Capital Increase the Effect Of Oda On Economic Gr...mentioning
confidence: 99%